Transcriptome Sequencing Highlights the Regulatory Role of DNA Methylation in Immune-Related Genes’ Expression of Chinese Oak Silkworm, Antheraea pernyi - Saima Kausar; Ruochen Liu; Isma Gul; Muhammad Nadeem Abbas; Hongjuan Cui (Insects, 2022)
Antheraea pernyi is an important lepidopteran used as a model insect species to investigate immune responses, development, and metabolism modulation. DNA methylation has recently been found to control various physiological processes throughout the life of animals; however, DNA methylation and its effect on the physiology of insects have been poorly investigated so far. In the present study, to better understand DNA methylation and its biological role in the immune system, we analyzed transcriptome profiles of A. pernyi pupae following DNA methylation inhibitor injection and Gram-positive bacteria stimulation. We then compared the profiles with a control group. We identified a total of 55,131 unigenes from the RNA sequence data. A comparison of unigene expression profiles showed that a total of 680 were up-regulated and 631 unigenes were down-regulated in the DNA-methylation-inhibition-bacteria-infected group compared to the control group (only bacteria-injected pupae), respectively. Here, we focused on the immune-related differentially expressed genes (DEGs) and screened 10 genes that contribute to immune responses with an up-regulation trend, suggesting that microbial pathogens evade host immunity by increasing DNA methylation of the host genome. Furthermore, several other unigenes related to other pathways were also changed, as shown in the KEGG analysis. Taken together, our data revealed that DNA methylation seems to play a crucial biological role in the regulation of gene expression in insects, and that infection may enhance the host genome DNA methylation by a yet-unknown mechanism.